INFORMATION SUPPORT IN INCREASING ELDERLY PARTICIPATION IN POSYANDU AT KARANG BARU HEALTH CENTRE - Sahara, Elvira; Rekawati, Etty (Universitas Muhammadiyah Ponorogo, 2025)
The activeness of the elderly coming to the posyandu has an important role for the health of the elderly. In this case, the factor that plays an important role in increasing the activeness of the elderly to the posyandu is information support from the family. This study aims to determine the role of information support from the family in increasing the activeness of the elderly to come to the posyandu. Through the use of correlative quantitative design through a cross-sectional approach with a sample of 370 elderly by random sampling, using a family support questionnaire and a list of elderly attendance at posyandu. This study shows that the frequency distribution of good information support (52.2%) and analysis of the significant relationship between information support and the activeness of the elderly in attending posyandu (p0.05). The important role of information support from the family in supporting the elderly to continue to actively participate in coming to posyandu. Recommendation: Family involvement is needed in providing health information to the elderly to support the elderly to actively attend posyandu as part of health interventions for the elderly